Evaluation of Isotope 32P Method to Mark Culex pipiens (Diptera: Culicidae) in a Laboratory - Chongxing Zhang; Guihong Shi; Yuqiang Zhao; Dongmei Yan; Huaiju Li; Hongmei Liu; Itsanun Wiwatanaratanabutr; Maoqing Gong (Tehran University of Medical Sciences, 2016)
Background: The aim of the current study was to develop a marking technique as an internal marker to mark post blood meal mosquitoes by using stable phosphate isotope 32P and determine the optimal concentration of it. Methods: An isotonic physiological saline solution, containing different concentration of radioactive isotope 32P-labeled disodium phosphate (Na2H32PO4) was injected into rabbits via the jugular vein in the laboratory. Emerged Cx. pipiens were marked after feeding on rabbit. At the same time, the labeled conditions of emerged Cx. pipiens were also measured by placing feces of No. 6 rabbit into containers with mosquito larvae and pupae inside. Results: According to the label condition of Cx. pipiens after taking blood and the effect of different dosage Na2H32PO4 on rabbit health, the optimal concentration of radioactive isotope was determined, that is, 0.1211 mCi/kg. By placing feces of No. 6 rabbit into containers with mosquito larvae and pupae inside, the emerged mosquitoes were also labeled. Therefore, feeding mosquitoes on the animal injected with radioactive Na2H32PO4 was more practical for detecting and tracing mosquitoes. Conclusion: The method was less time-consuming, more sensitive and safer. This marking method will facilitate post-bloodmeal studies of mosquitoes and other blood-sucking insects.